University and Universality. The Place and Role of the University of Pécs in Europe from the Middle Ages to present Day - L. Szögedi, Gabriella (Gerundium, 2019)
University and Universality. The Place and Role of the University of Pécs in Europe from the Middle Ages to present Day című kiadvány recenziója